New Insights on Mechanisms and Therapeutic Targets of Cerebral Edema - Shang, Pei; Zheng, Ruoyi; Wu, Kou; Yuan, Chao; Pan, Suyue (Current Neuropharmacology, 2024)
Cerebral Edema (CE) is the final common pathway of brain death. In severe neurological disease, neuronal cell damage first contributes to tissue edema, and then Increased Intracranial Pressure (ICP) occurs, which results in diminishing cerebral perfusion pressure. In turn, anoxic brain injury brought on by decreased cerebral perfusion pressure eventually results in neuronal cell impairment, creating a vicious cycle. Traditionally, CE is understood to be tightly linked to elevated ICP, which ultimately generates cerebral hernia and is therefore regarded as a risk factor for mortality. Intracranial hypertension and brain edema are two serious neurological disorders that are commonly treated with mannitol. However, mannitol usage should be monitored since inappropriate utilization of the substance could conversely have negative effects on CE patients. CE is thought to be related to blood-brain barrier dysfunction. Nonetheless, a fluid clearance mechanism called the glial-lymphatic or glymphatic system was updated. This pathway facilitates the transport of cerebrospinal fluid (CSF) into the brain along arterial perivascular spaces and later into the brain interstitium. After removing solutes from the neuropil into meningeal and cervical lymphatic drainage arteries, the route then directs flows into the venous perivascular and perineuronal regions. Remarkably, the dual function of the glymphatic system was observed to protect the brain from further exacerbated damage. From our point of view, future studies ought to concentrate on the management of CE based on numerous targets of the updated glymphatic system. Further clinical trials are encouraged to apply these agents to the clinic as soon as possible.
Keywords: blood-brain barrier